Application of a PM2.5 dispersion model in the Bangkok central business district for air quality management - Ratanavalachai, Thammaluck; Trivitayanurak, Win (Frontiers in Environmental Science, 2023)
Model simulations are conducted for fine particles diameter less than 2.5 microns (PM2.5) in the Chulalongkorn University area in the central business district of Bangkok, Thailand, where PM2.5 originating from road traffic is a recurring problem. For input to the American Meteorological Society / U.S. Environmental Protection Agency Regulatory Model (AERMOD), an hourly continuous vehicle type classified emissions inventory is developed based on local traffic observations and published emissions factors. The simulation accounts for advected-in PM2.5 by hourly measurements from upwind stations. The result reveals a hotspot location near a nearby expressway with PM2.5 concentration peaking at 1-hour and 24-hour averages of 344 and 130 µg m −3 , respectively. Source contribution analysis of the annual average PM2.5 at this hotspot suggests that the expressway contributes approximately 32% of the total PM2.5. Meanwhile, at receptor points farther from the expressway, ground-level urban roads contribute only 17.5% roadside PM2.5 concentrations, the remainder coming from outside the modeled area. A different source contribution breakdown by vehicle type suggests that heavy-duty vehicles contribute up to 21% of annual average PM2.5 at a location near the expressway. At a roadside receptor point farther from the expressway, the top contributors are light-duty (9%) and heavy-duty vehicles (6%). Advected-in PM2.5 dominates the overall PM2.5 concentrations, accounting for 64%-99% depending on the receptor point. The model performance for 24-hour average prediction is acceptable. A scenario study is also performed to compare the potential effectiveness of two PM2.5 abatement measures.